Precision gene editing technology and applications in nephrology. Issue 11 (November 2018) - WareJoncas, Zachary; Campbell, Jarryd; Martínez-Gálvez, Gabriel; Gendron, William; Barry, Michael; Harris, Peter; Sussman, Caroline; Ekker, Stephen
Abstract The expanding field of precision gene editing is empowering researchers to directly modify DNA. Gene editing is made possible using synonymous technologies: a DNA-binding platform to molecularly locate user-selected genomic sequences and an associated biochemical activity that serves as a functional editor. The advent of accessible DNA-targeting molecular systems, such as zinc-finger nucleases, transcription activator-like effectors (TALEs) and CRISPR–Cas9 gene editing systems, has unlocked the ability to target nearly any DNA sequence with nucleotide-level precision. Progress has also been made in harnessing endogenous DNA repair machineries, such as non-homologous end joining, homology-directed repair and microhomology-mediated end joining, to functionally manipulate genetic sequences. As understanding of how DNA damage results in deletions, insertions and modifications increases, the genome becomes more predictably mutable. DNA-binding platforms such as TALEs and CRISPR can also be used to make locus-specific epigenetic changes and to transcriptionally enhance or suppress genes. Although many challenges remain, the application of precision gene editing technology in the field of nephrology has enabled the generation of new animal models of disease as well as advances in the development of novel therapeutic approaches such as gene therapy and xenotransplantation. The application of precision gene editing has great potential to accelerate basic research and advance clinical practice in nephrology. Here, the authors discuss this technology and the challenges and potential of genome editing in the kidney. Key points Zinc-finger nucleases, transcription activator-like effector nucleases and CRISPR systems are powerful tools that are enabling new applications of genome engineering in diverse systems. Targeted double-stranded breaks in DNA activate diverse repair processes, such as non-homologous end joining, homology-directed repair and microhomology-mediated end joining, which can be utilized to modify the nucleotide sequence of DNA. Use of non-nuclease genomic tools enables the editing of single bases and locus-specific epigenetic targeting to modify gene expression. Applications of precision gene editing in nephrology include the generation of animal models to investigate kidney development and disease mechanisms as well as the development of targeted gene therapies. Genome editing in the kidney is challenging owing to anatomical barriers to gene delivery, limitations of vector size and immune responses against viral vectors, modified cells and editing proteins. Despite these challenges, precision gene editing has great potential to accelerate basic science in nephrology and to advance clinical practice through the development of novel therapies for renal diseases.